Characterization of Pure and Doped ZnO Nanostructured Powders elaborated in Solar Reactor - Schiopu, Adriana-Gabriela; Oproescu, Mihai; Iana, Vasile Gabriel; Moga, Sorin Georgian; Negrea, Denis Aurelian; Vilcoci, Denisa Stefania; Cirstea, Georgiana; Ducu, Catalin Marian; Iota, Miruna-Adriana (Engineering, Technology & Applied Science Research, 2024)
The synthesis of nano-oxides is an important field of nanotechnology, as these materials possess unique properties and applications. Several methods have been developed for synthesizing nano-oxides, each offering advantages and disadvantages depending on the desired material characteristics. Solar energy focused on solar reactors can be utilized for nano-oxide elaboration, offering a sustainable and environmentally friendly approach. The current article presents the research carried out for the elaboration of pure and doped nanostructured zinc oxides using solar energy. The morphostructural characteristics were determined by X-Ray Diffraction (XRD), Scanning Electron Microscopy (SEM), and the Brunauer-Emmett-Teller method. The attenuated total reflectance Fourier transform infrared spectroscopy confirmed the synthesis of pure and doped nanostructured ZnO. The optical properties were highlighted by UV-VIS Spectroscopy. The research points out that crystallite sizes vary between 37 and 51 nm due to the influence of doping metal. The morphology associated with these particles is predominantly whiskers with elongated parts between 0.18 and 1.4 um. Doping with Fe, Si, Yb, and Ce causes a wider band gap compared to pure ZnO nanoparticles. As solar energy becomes more accessible and efficient, solar-driven synthesis of pure and doped ZnO is poised to be a crucial factor in shaping the future of material science and technology.